Pelatihan Pemanfaatan Minyak Jelantah menjadi Sabun Cuci Padat bagi Ibu-Ibu PKK Dusun Banjaran Cengklik - Fitria Novitasari; Shinta Fauziah; Luthfia Ihza Hafidha; Amira Nadhifa Rahma; Nor Auliya; Luky Widiya Nafarinda; Anita Wulandari; Luthfi Rahman (BADAN PENERBIT STIEPARI PRESS, 2025)
Processing used cooking oil into solid laundry soap is an effective solution to reduce environmental pollution while increasing the added value of household waste. On July 25, 2025, a training was held in Banjaran Cengklik Hamlet, Cukilan Village, Suruh District, Semarang Regency, with participants from the Family Welfare Movement (PKK) women. The activity aimed to provide education on the dangers of used cooking oil for health and the environment, training in soap processing skills, and encouraging the application of the 3R principle (Reduce, Reuse, Recycle). The methods used included counseling, sweetening, and hands-on practice. The results showed an increase in participants' knowledge and skills in utilizing used cooking oil into ready-to-use products, which have the potential to be developed as a household business. This training contributed to family economic empowerment and increased public awareness of sustainable waste management. This training also opened up opportunities for participants to develop micro-enterprises based on environmentally friendly waste management. With the new skills acquired, PKK women can start their own production of solid laundry soap, which not only reduces hazardous waste but also increases family income. Ongoing support from relevant parties, such as the provision of raw materials, product marketing, and ongoing training, will further strengthen the program's success. Furthermore, increased public awareness of the importance of used cooking oil waste management is expected to foster a broader environmental culture in the region. This success can also serve as a model for other villages implementing similar programs, allowing for a broader positive impact. With an integrated approach, used cooking oil waste management can become an integral part of a sustainable development strategy at the local level.